2019
DOI: 10.15446/bitacora.v29n1.67325
|View full text |Cite
|
Sign up to set email alerts
|

Metropolización y organización funcional de sistemas urbanos intermedios. Gran La Serena, Concepción y Puerto Montt

Abstract: En Sudamérica existe un consenso relativo que asocia la expansión y la profundización del sistema neoliberal con la metropolización urbana, los sistemas polinucleares, impulsados por la tercerización de las economías urbanas, y la formación de nuevos centros de consumo y negocios fuera de los centros tradicionales, mientras estos últimos evidencian señas de obsolescencia funcional. Dicha visión compartida, surgida a partir del estudio de las capitales nacionales, suele extrapolarse a las ciudades intermedias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…The research in Chile showed that cities are vulnerable to multi-hazards, evidencing the neoliberal urban development policies implemented, which has led to drastic changes in land use that follow free-market rules, and anthropizing the environment in response to the economic growth framework considering risk factors in the process (Matus et al 2019 ). In the GC, urban growth and city expansion over wetlands and riverbeds have increased risk exposure, transferring the poorest to peripheral areas, while increasing their vulnerability to extreme events (Rojas et al 2017 ; Napadensky and Orellana 2018 ). This is evident in post-disaster scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The research in Chile showed that cities are vulnerable to multi-hazards, evidencing the neoliberal urban development policies implemented, which has led to drastic changes in land use that follow free-market rules, and anthropizing the environment in response to the economic growth framework considering risk factors in the process (Matus et al 2019 ). In the GC, urban growth and city expansion over wetlands and riverbeds have increased risk exposure, transferring the poorest to peripheral areas, while increasing their vulnerability to extreme events (Rojas et al 2017 ; Napadensky and Orellana 2018 ). This is evident in post-disaster scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante el carácter general de tales procesos, la mayoría de estudios se han desarrollado en referencia a Santiago (Cattaneo, 2011;De Mattos et al, 2016;Lukas & López-Morales, 2017). Existen, sin embargo, algunos trabajos recientes -aunque incipientes-que se interesan por otros sistemas metropolitanos de Chile, refiriéndose, por ejemplo, a una dispersión selectiva de los servicios hacia la periferia (Napadensky & Orellana, 2019) o a las dinámicas recientes en el Gran Valparaíso (Fuentes & Pezoa, 2017). Pese a que Pérez et al (2019) han estudiado el proceso de verticalización en un barrio determinado de Concepción, lo han hecho sin abarcar las dinámicas del conjunto del Área Metropolitana.…”
Section: Revisión De La Literatura: Crecimiento Urbano Y Mercado Inmobiliariounclassified
“…In the case of intermediate city systems, the work of Hidalgo, de Mattos and Arenas (2009) brings together research on the systems of San Felipe-Los Andes (Arenas, Hidalgo & Aliaga, 2009), Quillota-La Calera (Negrete & Hidalgo, 2009) and Rancagua-Machalí (Arenas, Hidalgo & Aliaga, 2009), but these are left at a regional analysis level, without going into depth about the morphological patterns of the Metropolitan setup. From a functional analysis, Napadensky & Orellana (2019) have explored the cases of Greater La Serena, Greater Concepción, and Greater Puerto Montt, finding divergent trends with large Latin-American cities. All in all, many authors concur that the research in this field is incipient and that the models which explain the phenomena are exploratory in nature (Garín, Salvo & Bravo, 2009;Henríquez, 2014).…”
Section: Referencias Bibliográficasmentioning
confidence: 99%